Integrate Education on Climate Change in Teaching and Leaning Biology at High School - Hung, Nguyen The; Quyen, Nguyen Thi (VNU Journal of Science: Education Research; Vol 34 No 2DO - 10.25073/2588-1159/vnuer.4134, 2018)
Currently, climate change is an enormous challenge to all humanity. However, the high school curriculum in Vietnam does not have the Education Climate Change subject. So education on climate change should be integrated in the teaching and learning of subjects. In high school curriculum, Biology has many advantages in the integration of education on climate change. Besides presenting theoretical basis for education on climate change in the teaching Biology (objective, principles and basic requirements of the selection methods of  integrating on education climate change, this aticle also introduces the design and teaching – leaning "Biogeochemical cycles and the biosphere" (Biology 12) by integrating education on climate change.